Radiocarbon and Indian archaeology : [papers and panel discussions] - Agrawal, D. P., 1935-; Ghosh, A. (Amalananda) (Tata Institute of Fundamental Research, 1973)
Papers read and panel discussions at a symposium organized to mark the tenth year of completion of the Radiocarbon Laboratory of the Tata Institute of Fundamental Research, Bombay.